Figurate erythematous lesion by Microsporum canis in immunosuppressed patient - Karine Paschoal Botelho; Yuri Coelho Soares; Deborah Pereira Gonçalves; Bárbara Lima Araújo Melo (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Dermatophytes are fungi capable of invading keratinized tissues. Isolation of the fungus with the culture is essential to guide the treatment, because there are more resistant species like Microsporum canis. The chronic use of corticosteroids leads to the deregulation of immunity, promoting atypical manifestations of infections. Topical antifungal therapy is often insufficient, requiring systemic medications. We describe the case of a patient undergoing systemic corticosteroid therapy with a large figurate lesion who presented complete response to exclusively topical treatment.